The Potential Association of Iron and Zinc Levels with Insulin Resistance in Type 2 Diabetes, Obesity, and Apparently Healthy Adults - Jbireal, J. M.; Fatimah Omar Hasan, (AlQalam Journal of Medical and Applied Sciences, 2025)
This narrative review explores the possible link between insulin resistance (IR) and alterations in iron and zinc status among individuals with type 2 diabetes mellitus (T2DM), obesity, and those considered healthy. Insulin resistance—characterized by a reduced cellular response to insulin—precedes the onset of T2DM and is influenced by metabolic, nutritional, and hormonal factors. Evidence suggests that iron and zinc, two essential trace elements with antioxidative and enzymatic functions, may play key roles in glucose homeostasis and insulin signaling. High iron levels have been associated with impaired insulin sensitivity, mitochondrial dysfunction, and adipose tissue inflammation, whereas iron deficiency may coexist with obesity due to inflammatory-mediated hepcidin activity. Zinc, crucial for insulin synthesis, storage, and secretion, is frequently reduced in metabolic disorders and may influence both insulin action and lipid metabolism. However, existing studies report mixed and sometimes conflicting findings. This review synthesizes data from research published between 2010 and 2025 and highlights that dysregulated iron and zinc levels may serve as surrogate markers of insulin resistance across various metabolic conditions. While these micronutrients show potential diagnostic and therapeutic relevance, further large-scale, well-designed studies are needed to confirm their roles and guide clinical applications.